The Effect of the Use of Information Technology, Social Media and Work Discipline on Employee Productivity at PT Kencana Sawit Indonesia Solok Selatan - Samsifren - Siska; Jumi - Jumi; Fatchun - Hasyim (Politeknik Negeri Semarang, 2021)
The aim of this study is to analyze the influence of Information Technology, Social Media, and Work Discipline on Employee Productivity at PT Kencana Sawit Indonesia South Solok. Data collection methods used are questionnaires and literature review. The questionnaire is using Agree-Disagree Scale with a scale of 10 points and the sample collection method used is total sampling with a sample of 50 employees at PT Kencana Sawit Indonesia. The analysis technique is using validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, T test, F test and coefficient of determination. Based on the calculations, regression equation obtained is Y = 0.602X1 + 0.364X2 + 0.562X3 + e, with a coefficient of determination is 68.4%. These results indicate that Information Technology (X1), Social Media (X2) and Work Discipline (X3) variables have a significant and positive effect on Employee Productivity (Y). This study only examines the influence of Information Technology, Social Media, and Work Discipline on Employee Productivity in industrial companies, to further research of the effect of Information Technology, Social Media, and Work Discipline on Employee Performance, besides that it can use research objects in other industries and can use samples of more than 50